2021
DOI: 10.1042/ebc20210023
|View full text |Cite
|
Sign up to set email alerts
|

Retromer dependent changes in cellular homeostasis and Parkinson's disease

Abstract: To date, mechanistic treatments targeting the initial cause of Parkinson’s disease (PD) are limited due to the underlying biological cause(s) been unclear. Endosomes and their associated cellular homeostasis processes have emerged to have a significant role in the pathophysiology associated with PD. Several variants within retromer complex have been identified and characterised within familial PD patients. The retromer complex represents a key sorting platform within the endosomal system that regulates cargo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 125 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, as part of the SNX-BAR heterodimer which itself is part of the retromer, SNX5 was particularly interesting. It is known that the retromer plays a role in the pathophysiology of PD (19)(20)(21). Mutations in an important component of the retromer, VPS35, are risk factors to develop PD, but the frequency of such mutations is not yet known (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as part of the SNX-BAR heterodimer which itself is part of the retromer, SNX5 was particularly interesting. It is known that the retromer plays a role in the pathophysiology of PD (19)(20)(21). Mutations in an important component of the retromer, VPS35, are risk factors to develop PD, but the frequency of such mutations is not yet known (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The dimer formed by SNX5 is responsible for recruiting retromer into the endosome and is an essential protein involved in intracellular and intracellular material transport and signal transduction [ 16 , 22 ]. In recent years, genomics animal and cell biology have shown that retromer-mediated protein transport defects in endosomal sorting are closely related to PD pathogenesis [ 15 , 23 , 24 ]. SNXs play a variety of roles in different aspects of endosomal transport, including the transport of endosomes to the trans-Golgi network, circulation to the cell surface, and endocytosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%